The effect of bull age on freeze-quality of beef semen - Hartman, Ashley; Muilenburg, S.; McCabe, Esther; Grieger, David M. (My University, 2018)
The age of beef bulls received for semen collection at commercial semen freezing facilities varies greatly. The duration of time bulls are housed at a facility prior to production of freeze-quality semen is also highly variable. The objective of this study was to evaluate the effect of age of beef sire on spermatozoa production in a commercial semen collection facility. Individual bulls were evaluated from a single facility over a five-year time period. Bulls included in the analysis represented various ages, breeds, and collection dates. The study included 1,812 bulls representing a total of 36,259 collections. All semen was evaluated using light microscope analysis by the same technician. The passing threshold for freeze-quality samples was 50% progressive motility, and less than 30% abnormal morphology with no more than 19% being primary abnormalities. On average bulls were 25.8 months old at time of admission and 27.0 months of age at first collection meeting the quality threshold. Bulls stayed for approximately 36.7 collections. There was a 0.64 correlation analysis between variables was conducted using Pearson’s correlation analysis in Excel. Between average units collected and the age of the bulls. The average number of collections prior to bulls successfully producing spermatozoa of freezing quality was 9.76. After an average of 10 collections, bulls over 27 months of age are likely to produce freezing quality semen. Once bulls began to produce freezing quality spermatozoa, they remained at the facility for approximately 9 collections. Of which they produced an average of 1,991 units of spermatozoa. While numerous bulls less than 27 months of age are in high demand for collection, they are less likely to produce spermatozoa meeting the thresholds of freezing quality.
Keywords: Fall 2018